Hybrid effects in the fracture toughness of polyvinyl butyral-based nanocomposites - Shemer, Eldad (2019)
Hybrid polyvinyl butyral (PVB) nanocomposite films comprising surface-treated carbon nanotubes (CNT-COOH) and nanoclays (NC) were tested for their “trouser-leg” fracture toughness in comparison to the values of the respective CNT and NC parent composites and to that of the pristine PVB film. Relative to the fracture toughness of the pristine PVB, the parent composites PVB/CNT-COOH-0.2% and PVB/NC-2% and the PVB/CNT-COOH-0.2%/NC-2% hybrid exhibited 105, 118, and 181% improvements, respectively. These were both impressive fracture toughness improvements and a significant hybrid effect – the latter being only slightly lower than the nominal maximum effect of 223% based on the combined improvements of the parent composites. Part of the samples was tested qualitatively by ball impact test of ballistic glass samples with relevant films. Among these samples, the hybrid film presented the best result. A significant linear correlation between fracture surface energy and roughness values was taken to reflect a fracture resistance mechanism of crack front slowdown by its interactions with nanoparticles.